Empathy and Social Support for Special Needs Children at Leleani Special School (SLB) 1 - Lessil, Constansa G. (Interdisciplinary Social Studies, 2023)
Background: Humans are social creatures who cannot live alone in activities to meet the needs of daily life. Similarly, children with special needs who have physical and mental limitations, of course, their lives are greatly influenced by attention and empathy with support from the surrounding community. Aim: The research would like to analyze empathy and social support for special needs children at Leleani Special School (SLB) 1 in Ambon. Method: This research is a limited survey research conducted on 45 respondents, categorized into 15 parents, teachers/administrators and the community around Leleani 1 Special School (SLB). Respondents were drawn by stratified random sampling and then analyzed qualitatively and quantitatively. Findings: The results showed that empathetic responses and social support between parents, teachers and the surrounding community when compared in general did not have a significant difference. Partially, differences occur in information support and affective components of teacher empathy when compared to the surrounding community.